Unveiling activity patterns of the deer Odocoileus virginianus (Artiodactyla: Cervidae) and its predators in Mexico’s Arid Region - Plata Pérez, Fernando; Urbina Flores, Diana Patricia; Villarreal Espino Barros, Oscar Agustin; Gloria Trujillo, Adrián; Mendoza Martínez, German David (Revista de Biología Tropical, 2024)
Introduction: Size, predator presence, and habitat nutritional quality influence herbivorous species’ activity patterns and resource utilization. Objectives: This study aims to determine the relative abundance and activity patterns of white-tailed deer (Odocoileus virginianus) and their main predators. Methods: The study was conducted in the WMU "Bienes Comunales Santa Cruz Nuevo" in Totoltepec de Guerrero, Puebla, Mexico. Twenty-two quadrants were randomly selected, and camera traps were installed. Over a two-year period (2018-2020), wildlife visits were recorded to estimate the relative abundance index (RAI), activity patterns, and overlap coefficient (Dhat1) of white-tailed deer and their predators based on their activity schedule. Results: The estimated RAI for deer was 7.2%, while it was 3.4% for coyotes (Canis latrans), 2.3% for bobcats (Lynx rufus), and 0.14% for pumas (Puma concolor). White-tailed deer were observed in 31% of the camera traps, while coyotes were captured in 68% of them. The overlap of the activity schedule, Dhat1, between deer and coyotes was 0.18. In contrast, the activity overlap between foxes and deer was higher (Dhat1: 0.2979; EE 0.037) based on the analysis of variance. The activity pattern of coyotes indicated they were crepuscular, with increased activity during the afternoon and night. However, an increase in activity synchronized with deer’s patterns was also observed. The bobcat coincided with deer in 10% of the cameras, but due to the limited number of observations, it was not possible to estimate the activity overlap between these species. Conclusions: The activity overlap between white-tailed deer and foxes is more significant than that of deer and coyotes in this region. The activity overlap between deer and coyotes is lower compared to other parts of the world.